Fear of missing out pada remaja di Surabaya: Bagaimana peranan regulasi diri? - Veni Anjar Wati; Herlan Pratikto; Akta Ririn Aristawati (INNER: Journal of Psychological Research, 2023)
Abstract This study aims to determine the relationship between self-regulation and fear of missing out among adolescents in Surabaya. This study uses quantitative methods to achieve research objectives. The research subjects used in this study were teenagers in Surabaya aged 12-18 years, totaling 153 people. This research is a population study research. The measuring tool uses a self-regulation scale with the fear of missing out in adolescents. The research data were analyzed using the Product Moment correlation test. The results of data analysis calculations show a product-moment correlation coefficient of -0.331 with a significance level of p = 0.000 <0.05, this result means that there is a significant negative relationship between self-regulation and fear of missing out in adolescents. From these results, it can be interpreted that the higher the self-regulation the lower the effect of missing output, and vice versa. The hypothesis that says there is a relationship between self-regulation and fear of missing out in adolescents is accepted. The hypothesis which states that there is a relationship between self-regulation and fear of missing out among adolescents in Surabaya is accepted. Keywords: Self-regulation, Fear of missing out, Teenagers.